Chromosomal destabilization during gene amplification. - Ruiz, J C (1990)
Acentric extrachromosomal elements, such as submicroscopic autonomously replicating circular molecules (episomes) and double minute chromosomes, are common early, and in some cases initial, intermediates of gene amplification in many drug-resistant and tumor cell lines. In order to gain a more complete understanding of the amplification process, we investigated the molecular mechanisms by which such extrachromosomal elements are generated and we traced the fate of these amplification intermediates over time. The model system consists of a Chinese hamster cell line (L46) created by gene transfer in which the initial amplification product was shown previously to be an unstable extrachromosomal element containing an inverted duplication spanning more than 160 kilobases (J. C. Ruiz and G. M. Wahl, Mol. Cell. Biol. 8:4302-4313, 1988). In this study, we show that these molecules were formed by a process involving chromosomal deletion. Fluorescence in situ hybridization was performed at multiple time points on cells with amplified sequences. These studies reveal that the extrachromosomal molecules rapidly integrate into chromosomes, often near or at telomeres, and once integrated, the amplified sequences are themselves unstable. These data provide a molecular and cytogenetic chronology for gene amplification in this model system; an early event involves deletion to generate extrachromosomal elements, and subsequent integration of these elements precipitates a cascade of chromosome instability.